2002
DOI: 10.1017/s1355617701020069
|View full text |Cite
|
Sign up to set email alerts
|

Paired associate performance in the early detection of DAT

Abstract: Subjects underwent longitudinal neuropsychological assessment in order to retrospectively determine which measures of cognitive function best predicted later development of dementia of the Alzheimer type (DAT). Three groups of subjects were studied: normal controls, patients with early DAT, and questionable dementia subjects (QD). All subjects were assessed using a battery of standard neuropsychological measures and two subtests from the Cambridge Neuropsychological Test Automated Battery (CANTAB), paired asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 52 publications
8
102
0
2
Order By: Relevance
“…Results indicated a A visuospatial memory measure that is sensitive to cognitive decline (Fowler et al 2002). Rey-Osterrieth Complex Figure A measure of visual memory sensitive to brain injury (Berry et al 1991 (Millis et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated a A visuospatial memory measure that is sensitive to cognitive decline (Fowler et al 2002). Rey-Osterrieth Complex Figure A measure of visual memory sensitive to brain injury (Berry et al 1991 (Millis et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17] Of relevance here, several recent reports suggest that persons with a diagnosis of MCI show a disproportionate decrease in relational memory, 18,19 and that the relational memory deficits in this group can be predictive of future cognitive impairment. 20,21 The current study was the first to examine whether dissociations between item and relational memory might exist in persons with multiple sport-related concussions. Because of the established link between multiple concussions and MCI diagnosis, it is possible that increased concussion history will be associated with disproportionate deficits in associative memory.…”
Section: Introductionmentioning
confidence: 94%
“…Studies that have used the Paired Associate Learning Task (PAL) from the Cambridge Neuropsychological Testing Automated Battery (CANTAB; Cambridge Cognition Place, UK) suggest that patients with AD (Lee et al, 2003) and patients with MCI (de Rover et al, 2011) have deficits in associative memory. Furthermore, Fowler et al (2002) found that performance on the PAL was impaired in early-stage AD patients, even before standard neuropsychological measures detected any deterioration. Along the same lines, Pariente et al (2005) found that AD patients' performance was reduced in a face-name association task.…”
Section: Introductionmentioning
confidence: 98%